Topologi Redundansi Link Untuk Keamanan Serta Mitigasi Ketersediaan Jaringan Komputer Menggunakan Rapid Spanning Tree Protocol - Mohammad Taufan Asri Zaen; Ahmad Tantoni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The frequent occurrence of natural disasters requires telecommunications companies to require a backup internet backbone line if the telecommunications infrastructure is damaged/disconnected due to natural disasters. Reporting from inet.detik.com APJII revealed that the Jakarta-Singapore fiber optic network had broken, which had an impact on internet services in Indonesia. Fiber optic repair can take up to 2-3 weeks requiring network backup, the main solution for network backup with satellite, but problems will arise when configuration for satellite lines takes 1-2 days. Problems arise again when combined between fiber optic internet lines and satellite internet lines which cause the looping network to create network disturbances, to maintain interference, a spanning tree protocol method is needed to backup lines automatically and create link redundancy if one of the lines is problematic or disconnected. The purpose of this study is to design a link redundancy topology for security and mitigation of network availability using the rapid spanning tree protocol (RSTP) with router rb750gr3, switch rb260gs and switch dgs-108. In the RSTP network topology, it is designed with 3 redundant lines connected between the rb260gs switch and the dgs-108 switch, with an on-stick router rb750gr3 and is designed with 6 access mode vlan lines. In testing the inter-vlan network, RSTP terminates the redundancy link and then uses the ping command at the command prompt to determine how many minutes to backup the link. The NDLC method is used in determining how many seconds to backup this redundancy link using. The results of testing the link termination ether2-switch-mikrotik and ether1-switch-dlink using the